Preparation method of thermal barrier coating
By filling nano-level heat-absorbing materials with vacuum impregnation process in the thermal barrier coating, the thermal shock stability problem of the thermal barrier coating under high temperature impact is solved, significantly improving the thermal stability and thermal insulation effect of the coating, and extending the The service life of the coating.
Patent Information
- Application Number
- CN202411310213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-19
AI Technical Summary
When the existing thermal barrier coatings face sudden changes in temperature such as combustion chambers, the thermal shock stability is poor, resulting in a shortening of the coating life.
The thermal insulation layer with longitudinal cracks is sprayed by an ion spraying process, and the heat-absorbing material is filled in the longitudinal cracks by a vacuum impregnation process, including strontium, zirconium, neodymium, samarium, europium, gadolinium, dysprosium, erbium, ytterbium, lutetium or yttrium The oxides are processed by combining high-temperature treatment, acid treatment and ultrasonic dispersion treatment to process kaolin to form nanoscale heat-absorbing materials and are filled into longitudinal cracks to improve thermal shock stability.
By filling the heat-absorbing material, the thermal stability and thermal insulation effect of the thermal barrier coating are significantly improved. The heat-absorbing material can absorb a large amount of heat during high temperature impact, forming a buffering effect, and extending the service life of the coating.
Smart Images

Figure CN119162533A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a method for preparing a thermal barrier coating. Background Art
[0002] Thermal barrier coatings are commonly used in aerospace engines and turbine blades, and have excellent thermal insulation properties. However, when faced with sudden temperature increases such as combustion in the combustion chamber, thermal shock will occur, shortening the coating life.
[0003] Therefore, in view of the above shortcomings, a thermal shock coating with excellent thermal shock stability is desired. Summary of the invention
[0004] The embodiment of the present invention provides a method for preparing a thermal barrier coating, which has excellent heat insulation and thermal shock stability.
[0005] An embodiment of the present invention provides a method for preparing a thermal barrier coating, comprising:
[0006] Spraying the slurry onto the substrate to be protected by an ion spraying process to obtain a thermal insulation layer with longitudinal cracks; wherein the longitudinal cracks are perpendicular to the thermal insulation layer, one end of the longitudinal cracks extends to the surface of the thermal insulation layer, and the other end is located inside the thermal insulation layer, and the slurry includes a thermal barrier material, and the thermal barrier material includes an oxide of at least one of strontium, zirconium, neodymium, samarium, europium, gadolinium, dysprosium, erbium, ytterbium, lutetium or yttrium;
[0007] The heat absorbing material is filled into the longitudinal cracks by using a vacuum impregnation process.
[0008] In a possible design, before the vacuum impregnation process is used to fill the heat absorbing material into the longitudinal crack, the method further includes:
[0009] The kaolin is processed by high temperature treatment, acid treatment and ultrasonic dispersion treatment in sequence to obtain nano-grade kaolin;
[0010] Mixing nano-sized kaolin with a liquid to obtain a heat absorbing material;
[0011] The method of filling the longitudinal crack with the heat absorbing material by a vacuum impregnation process comprises:
[0012] Place the thermal insulation layer in a vacuum negative pressure environment;
[0013] Covering the heat absorbing material on the entire upper portion of the heat insulation layer;
[0014] Applying positive pressure to the heat absorbing material and performing ultrasonic dispersion treatment;
[0015] The heat absorbing material is made to fill the longitudinal crack.
[0016] In one possible design, the liquid includes water;
[0017] After allowing the heat absorbing material to fill the longitudinal crack, the method further comprises:
[0018] The water in some longitudinal cracks can be precisely evaporated by controlling the temperature, humidity and heating time.
[0019] In a possible design, the liquid includes a salt solution; wherein the salt solution includes a phosphate solution, a chloride solution, and a fluoride solution;
[0020] After allowing the heat absorbing material to fill the longitudinal crack, the method further comprises:
[0021] Prepare a salt solution with a concentration lower than the preset concentration;
[0022] The water in the salt solution in some longitudinal cracks is precisely evaporated by controlling the temperature, humidity and heating time, so that the concentration of the salt solution is a preset concentration.
[0023] In a possible design, the volume of the longitudinal cracks accounts for 20-30% of the volume of the thermal insulation layer.
[0024] In a possible design, the longitudinal depth of the longitudinal crack is not less than 65-90% of the thickness of the thermal insulation layer.
[0025] In one possible design, the heat absorbing material includes at least one of a fatty acid solid-liquid phase change material and an alcohol solid-liquid phase change material;
[0026] The method of filling the longitudinal crack with the heat absorbing material by a vacuum impregnation process comprises:
[0027] Heating the solid-liquid phase change material in a vacuum environment to make it in liquid phase;
[0028] The heat insulation layer is soaked with a liquid solid-liquid phase change material, and a positive pressure is applied to the liquid solid-liquid phase change material so that the liquid solid-liquid phase change material is immersed in the longitudinal crack;
[0029] After the longitudinal cracks are filled, they are taken out after the temperature and pressure are reduced.
[0030] In a possible design, the slurry is sprayed on the substrate to be protected by an ion spraying process to obtain a thermal insulation layer with longitudinal cracks, including:
[0031] The slurry including a plurality of vacuum balls is sprayed on the substrate to be protected by using an ion spraying process to obtain a heat insulation layer with longitudinal cracks and vacuum balls.
[0032] In a possible design, the shell of the vacuum ball is made of silicon dioxide and / or aluminum oxide, and the outer diameter of the vacuum ball is 5 to 10 μm.
[0033] In a possible design, after the heat absorbing material is filled into the longitudinal crack by the vacuum impregnation process, the method further includes:
[0034] A sealing layer is prepared by plasma spraying on the side of the thermal insulation layer away from the protective substrate; wherein the preparation material of the sealing layer includes the thermal barrier material, and the sealing layer is used to seal the opening of the longitudinal crack located on the surface of the thermal insulation layer;
[0035] The thickness of the heat insulation layer is 50-500 μm, and the thickness of the sealing layer is 5-20 μm.
[0036] Compared with the prior art, the present invention has at least the following beneficial effects:
[0037] By controlling the slurry composition and process parameters of the plasma spraying process, longitudinal cracks can be obtained. The longitudinal cracks can improve the mechanical properties of the coating and the thermal insulation effect. In order to improve its thermal shock stability, the longitudinal cracks are filled with heat-absorbing materials. In order to allow the heat-absorbing materials to be smoothly immersed in the longitudinal cracks, the vacuum impregnation process is used to fill the heat-absorbing materials into the longitudinal cracks. The heat-absorbing materials have excellent heat absorption properties and large latent heat. When the thermal barrier coating is subjected to an instantaneous high-temperature shock, the heat-absorbing materials can absorb a large amount of heat, forming a buffering effect of the thermal shock, thereby achieving the effect of improving the thermal stability of the thermal barrier coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 is a flow chart of a method for preparing a thermal barrier coating provided by an embodiment of the present invention;
[0040] Figure 2 It is a schematic diagram of the structure of a thermal barrier coating provided in an embodiment of the present invention.
[0041] In the figure:
[0042] 1- Thermal insulation layer;
[0043] 11-longitudinal cracks;
[0044] 12- heat absorbing material;
[0045] 13- Vacuum ball;
[0046] 2- Sealing layer;
[0047] 100-base. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance; unless otherwise specified or explained, the term "multiple" refers to two or more; the terms "connected" and "fixed" should be understood in a broad sense, for example, "connected" can be a fixed connection, a detachable connection, an integral connection, or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0050] In the description of this specification, it should be understood that the directional words such as "upper" and "lower" described in the embodiments of the present invention are described at the angles shown in the drawings and should not be understood as limiting the embodiments of the present invention. In addition, in the context, it should also be understood that when it is mentioned that an element is connected to another element "upper" or "lower", it can not only be directly connected to another element "upper" or "lower", but also indirectly connected to another element "upper" or "lower" through an intermediate element.
[0051] As mentioned above, the thermal barrier material can play a significant role in heat insulation at a thickness of tens to hundreds of microns, and can protect the substrate to be protected by the thermal barrier coating from or from being affected by a small amount of high temperature. Although the thermal barrier coating in the prior art can achieve a good insulation effect, its thermal shock stability is poor when the ambient temperature rises instantly, which may lead to a decrease in the service life of the coating. In order to solve the above problems, the present invention proposes a thermal barrier coating with a heat insulation layer having longitudinal cracks.
[0052] Please refer to Figure 1 and Figure 2 , an embodiment of the present invention provides a method for preparing a thermal barrier coating, comprising:
[0053] The slurry is sprayed on the substrate 100 to be protected by an ion spraying process to obtain a thermal insulation layer 1 with longitudinal cracks; wherein the longitudinal cracks 11 are perpendicular to the thermal insulation layer 1, one end of the longitudinal cracks extends to the surface of the thermal insulation layer 1, and the other end is located inside the thermal insulation layer 1, and the slurry includes a thermal barrier material, and the thermal barrier material includes an oxide of at least one of strontium, zirconium, neodymium, samarium, europium, gadolinium, dysprosium, erbium, ytterbium, lutetium or yttrium;
[0054] The heat absorbing material 12 is filled into the longitudinal cracks by a vacuum impregnation process.
[0055] By controlling the slurry composition and process parameters of the plasma spraying process, longitudinal cracks can be obtained. The longitudinal cracks can improve the mechanical properties of the coating and the thermal insulation effect. In order to improve its thermal shock stability, the longitudinal cracks are filled with heat absorbing materials 12. In order to make the heat absorbing materials 12 smoothly penetrate into the longitudinal cracks 11, the vacuum impregnation process is used to fill the heat absorbing materials 12 into the longitudinal cracks 11. The heat absorbing materials 12 have excellent heat absorption performance and large latent heat. When the thermal barrier coating is subjected to an instantaneous high temperature shock, the heat absorbing materials 12 can absorb a large amount of heat, forming a buffering effect of the thermal shock, thereby achieving the effect of improving the thermal stability of the thermal barrier coating.
[0056] In some embodiments of the present invention, before the vacuum impregnation process is used to fill the heat absorbing material 12 into the longitudinal crack, the method further includes:
[0057] The kaolin is processed by high temperature treatment, acid treatment and ultrasonic dispersion treatment in sequence to obtain nano-grade kaolin;
[0058] Mixing nano-sized kaolin and liquid to obtain a heat absorbing material 12;
[0059] Filling the heat absorbing material 12 into the longitudinal cracks by a vacuum impregnation process, including:
[0060] Placing the thermal insulation layer 1 in a vacuum negative pressure environment;
[0061] Cover the entire upper portion of the heat-insulating layer 1 with a heat-absorbing material 12;
[0062] Applying positive pressure to the heat absorbing material 12 and performing ultrasonic dispersion treatment;
[0063] The heat absorbing material 12 is made to fill the longitudinal cracks 11 .
[0064] In this embodiment, in order to fill the longitudinal crack 11 with the heat absorbing material 12, all gases are first exhausted under vacuum negative pressure to place the longitudinal crack 11 in a vacuum environment, which facilitates the heat absorbing material 12 to enter the longitudinal crack 11. Then, the heat absorbing material 12 is heated to cover the entire thermal insulation layer 1, and the heat absorbing material 12 near the longitudinal crack 11 partially enters the longitudinal crack 11. A positive pressure is applied to the heat absorbing material 12 covering the thermal insulation layer 1, and ultrasonic waves are applied to fill the longitudinal crack 11 with the heat absorbing material 12.
[0065] In this embodiment, the heat absorbing material 12 can be kaolin that absorbs liquid. The kaolin has nano-scale particle size, water absorption and water retention properties, and heat insulation properties. It can absorb and store liquid with large latent heat while ensuring the insulation performance of the heat insulation layer 1, so as to absorb heat and buffer during high heat shock. Natural kaolin can be obtained into a nano-scale porous nanostructure through high temperature treatment, acid treatment and ultrasonic dispersion. Its nano-scale particle size can enter the micron-scale longitudinal cracks 11 and absorb high latent heat liquid through capillary water absorption.
[0066] In some embodiments of the invention, the liquid comprises water;
[0067] After the heat absorbing material 12 fills the longitudinal crack 11, the method further comprises:
[0068] The water in the longitudinal cracks 11 is precisely evaporated by controlling the temperature, humidity and heating time.
[0069] In this embodiment, the liquid may be water, which has a relatively high latent heat.
[0070] It should be noted that the space inside the longitudinal crack 11 is larger than the volume of the heat-absorbing material 12 itself. This arrangement ensures that the heat-absorbing material 12 does not completely occupy the entire space in the longitudinal crack 11, and reserves space for the heat-absorbing phase change expansion of the heat-absorbing material 12, thereby preventing the heat-absorbing material 12 from widening the longitudinal crack 11 after the heat-absorbing phase change expansion, thereby ultimately shortening the coating life.
[0071] After the heat absorbing material 12 fills the longitudinal cracks 11, the heat absorbing material 12 often completely fills the cracks. In order to make the heat absorbing material 12 partially occupy the longitudinal cracks 11, part of the liquid can be removed after the heat absorbing material 12 completely fills the cracks. Specifically, when the liquid is water, the water in part of the longitudinal cracks 11 can be precisely evaporated by controlling the temperature, humidity and heating time.
[0072] In some embodiments of the present invention, the liquid includes a salt solution; wherein the salt solution includes a phosphate solution, a chloride solution, and a fluoride solution;
[0073] After the heat absorbing material 12 fills the longitudinal crack 11, the method further comprises:
[0074] Prepare a salt solution with a concentration lower than the preset concentration;
[0075] The water in the salt solution in some longitudinal cracks 11 is precisely evaporated by controlling the temperature, humidity and heating time, so that the concentration of the salt solution is a preset concentration.
[0076] Preferably, the liquid is a salt solution, which has the advantage of reducing thermal conductivity in addition to having high latent heat. As described above, in order to prevent the salt solution from filling up the longitudinal cracks 11, when the liquid is a salt solution, a salt solution with a concentration lower than a preset concentration can be prepared first, and then the water in the salt solution in part of the longitudinal cracks 11 can be precisely evaporated by controlling the temperature, humidity and heating time to increase the concentration and reduce the volume.
[0077] In some embodiments of the present invention, the volume of the longitudinal cracks 11 accounts for 20-30% of the volume of the thermal insulation layer 1 .
[0078] In this embodiment, when the longitudinal cracks 11 are within the above volume fraction range, the longitudinal cracks 11 absorb the heat absorbing material 12 and the heat insulation layer 1 has good thermal shock stability and a long service life.
[0079] In some embodiments of the present invention, the depth of the longitudinal crack 11 is not less than 65-90% of the thickness of the thermal insulation layer 1 .
[0080] In this embodiment, the greater longitudinal depth can accommodate more heat-absorbing materials 12 and greatly improve the thermal shock stability, but the longitudinal crack 11 cannot completely penetrate the thermal insulation layer 1. If it completely penetrates, the service life of the thermal insulation layer 1 will be reduced.
[0081] In some embodiments of the present invention, the heat absorbing material 12 includes at least one of a fatty acid solid-liquid phase change material and an alcohol solid-liquid phase change material;
[0082] Filling the heat absorbing material 12 into the longitudinal cracks by a vacuum impregnation process, including:
[0083] Heating the solid-liquid phase change material in a vacuum environment to make it in liquid phase;
[0084] The heat insulation layer 1 is soaked with a liquid solid-liquid phase change material, and a positive pressure is applied to the liquid solid-liquid phase change material so that the liquid solid-liquid phase change material is immersed in the longitudinal crack 11;
[0085] After the longitudinal crack 11 is filled, it is taken out after the temperature and pressure are lowered.
[0086] In this embodiment, the heat absorbing material 12 can be at least one of a fatty acid solid-liquid phase change material and an alcohol solid-liquid phase change material. Both the fatty acid cracking solid-liquid phase change material and the alcohol solid-liquid phase change material have high latent heat and can absorb more heat during phase change. The two have good miscibility, and the application of the two can further expand the temperature range of adjusting the phase change.
[0087] When the solid-liquid phase change material is filled in the longitudinal crack 11, in order to avoid the solid-phase solid-liquid phase change material absorbing heat and expanding the phase change, and to expand the longitudinal crack 11, it is necessary to reserve expansion space in the longitudinal crack 11, and the longitudinal crack 11 can be filled in a high-temperature vacuum environment. Specifically, the solid-liquid phase change material is heated in a vacuum environment to be in a liquid phase, and the vacuum environment prevents its oxidation. The liquid-phase solid-liquid phase change material is used to soak the thermal insulation layer 1, and a positive pressure is applied to the liquid-phase solid-liquid phase change material, so that the liquid-phase solid-liquid phase change material is immersed in the longitudinal crack 11. After the longitudinal crack 11 is filled, the temperature and pressure are reduced, and the material is taken out. At this time, the solid-liquid phase change material shrinks to a solid phase and is located inside the longitudinal crack 11, and does not completely fill the longitudinal crack 11, leaving expansion space for the endothermic phase change in the later use stage.
[0088] In some embodiments of the present invention, the slurry is sprayed on the substrate 100 to be protected by an ion spraying process to obtain a heat insulation layer 1 with longitudinal cracks, including:
[0089] The slurry including the plurality of vacuum balls 13 is sprayed onto the substrate 100 to be protected by using an ion spraying process, so as to obtain a heat insulation layer 1 having longitudinal cracks and the vacuum balls 13 .
[0090] In this embodiment, in order to further increase the thermal insulation performance of the thermal barrier coating, a plurality of vacuum balls 13 are further provided in the thermal insulation layer 1. The interior of the vacuum balls 13 is a vacuum environment, and the vacuum cannot conduct heat, which further increases the thermal insulation performance of the thermal insulation layer 1. In addition, under the same heat transfer path, the smaller the cross-sectional area of heat transfer, the slower the heat conduction speed. The path length of the heat from the outside to the substrate 100 layer is the thickness of the coating. However, in the thermal insulation layer 1 provided with the vacuum balls 13, due to the presence of the vacuum balls 13, the cross-sectional area of the surface parallel to the substrate 100 is reduced, which further increases the thermal insulation effect.
[0091] It should be noted that, since the vacuum balls 13 have a small particle size and are round in shape, they have strong compressive strength and can increase the compressive strength of the thermal insulation layer 1 itself.
[0092] In some embodiments of the present invention, the shell of the vacuum ball 13 is made of silicon dioxide and / or aluminum oxide, and the outer diameter of the vacuum ball 13 is 5-10 μm.
[0093] In this embodiment, the shell of the vacuum ball 13 is made of heat-insulating material, which can ensure its heat-insulating effect. At the same time, the material itself has strong strength. The outer diameter of the vacuum ball 13 within the above range can take into account both strength and heat-insulating effect.
[0094] In some embodiments of the present invention, after the heat absorbing material 12 is filled into the longitudinal cracks by using a vacuum impregnation process, the method further includes:
[0095] A sealing layer 2 is prepared by plasma spraying on a side of the thermal insulation layer 1 away from the protective substrate 100; wherein the preparation material of the sealing layer 2 includes a thermal barrier material, and the sealing layer 2 is used to seal the opening of the longitudinal crack 11 located on the surface of the thermal insulation layer 1;
[0096] The thickness of the heat insulating layer 1 is 50 to 500 μm, and that of the sealing layer 2 is 5 to 20 μm.
[0097] It can be understood that the area of the longitudinal crack 11 located on the surface is extremely small. During its operation, the internal heat-absorbing material 12 is almost not in contact with the air, and the degree of oxidation is relatively small. However, in order to further increase its oxidation resistance at high temperatures and increase its service life, a sealing layer 2 can be provided on the outside of the insulation layer 1 to isolate the longitudinal crack 11 from the internal and external environments.
[0098] It should be noted that after obtaining the heat insulating layer 1 filled with the heat absorbing material 12 , the sealing layer 2 can also be sprayed in an oxygen-free environment using the ion spraying technology.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a thermal barrier coating, characterized in that: include: The slurry is sprayed on the substrate to be protected by an ion spraying process to obtain a thermal insulation layer with longitudinal cracks; wherein the longitudinal cracks are perpendicular to the thermal insulation layer, one end of the longitudinal cracks extends to the surface of the thermal insulation layer, and the other end is located inside the thermal insulation layer, and the slurry includes a thermal barrier material, and the thermal barrier material includes an oxide of at least one of strontium, zirconium, neodymium, samarium, europium, gadolinium, dysprosium, erbium, ytterbium, lutetium or yttrium; The heat absorbing material is filled into the longitudinal cracks by using a vacuum impregnation process.
2. The preparation method according to claim 1, characterized in that: Before the vacuum impregnation process is used to fill the heat absorbing material into the longitudinal crack, the method further comprises: The kaolin is processed by high temperature treatment, acid treatment and ultrasonic dispersion treatment in sequence to obtain nano-grade kaolin; Mixing nano-sized kaolin with a liquid to obtain a heat absorbing material; The method of filling the longitudinal crack with the heat absorbing material by a vacuum impregnation process comprises: Place the thermal insulation layer in a vacuum negative pressure environment; Covering the heat absorbing material on the entire upper portion of the heat insulation layer; Applying positive pressure to the heat absorbing material and performing ultrasonic dispersion treatment; The heat absorbing material is made to fill the longitudinal crack.
3. The preparation method according to claim 2, characterized in that: The liquid includes water; After allowing the heat absorbing material to fill the longitudinal crack, the method further comprises: The water in some longitudinal cracks is evaporated by controlling the temperature, humidity and heating time.
4. The preparation method according to claim 2, characterized in that: The liquid includes a salt solution; wherein the salt solution includes a phosphate solution, a chloride solution and a fluoride solution; After allowing the heat absorbing material to fill the longitudinal crack, the method further comprises: Prepare a salt solution with a concentration lower than the preset concentration; The water in the salt solution in some longitudinal cracks is evaporated by controlling the temperature, humidity and heating time, so that the concentration of the salt solution is a preset concentration.
5. The preparation method according to claim 1, characterized in that: The volume of the longitudinal cracks accounts for 20-30% of the volume of the thermal insulation layer.
6. The preparation method according to claim 1, characterized in that: The longitudinal depth of the longitudinal crack is not less than 65-90% of the thickness of the thermal insulation layer.
7. The preparation method according to claim 1, characterized in that: The heat absorbing material comprises at least one of a fatty acid solid-liquid phase change material and an alcohol solid-liquid phase change material; The method of filling the longitudinal crack with the heat absorbing material by a vacuum impregnation process comprises: Heating the solid-liquid phase change material in a vacuum environment to make it in liquid phase; The heat insulation layer is soaked with a liquid solid-liquid phase change material, and a positive pressure is applied to the liquid solid-liquid phase change material so that the liquid solid-liquid phase change material is immersed in the longitudinal crack; After the longitudinal cracks are filled, they are taken out after the temperature and pressure are reduced.
8. The preparation method according to claim 1, characterized in that: The method of spraying the slurry on the substrate to be protected by an ion spraying process to obtain a heat insulation layer with longitudinal cracks comprises: The slurry including a plurality of vacuum balls is sprayed on the substrate to be protected by using an ion spraying process to obtain a heat insulation layer with longitudinal cracks and vacuum balls.
9. The preparation method according to claim 8, characterized in that: The shell of the vacuum ball is made of silicon dioxide and / or aluminum oxide, and the outer diameter of the vacuum ball is 5 to 10 μm.
10. The preparation method according to claim 1, characterized in that: After the heat absorbing material is filled into the longitudinal crack by the vacuum impregnation process, the method further comprises: A sealing layer is prepared by plasma spraying on the side of the thermal insulation layer away from the protective substrate; wherein the preparation material of the sealing layer includes the thermal barrier material, and the sealing layer is used to seal the opening of the longitudinal crack located on the surface of the thermal insulation layer; The thickness of the heat insulation layer is 50-500 μm, and the thickness of the sealing layer is 5-20 μm.
Citation Information
Patent Citations
Postprocessing method for improving heat insulating property of ceramic heat barrier coating
CN101357855A
Preparation method of thermal barrier coating and thermal barrier coating prepared through preparation method
CN108441806A
Method for improving high temperature resistance and corrosion resistance of thermal barrier coating
CN112962050A
Low thermal conductivity thermal barrier coating with vertical crack structure and preparation method thereof
CN114015963A
Toughening and lubricating function integrated thermal spraying ceramic coating as well as preparation method and application thereof
CN114164387A
